The Impact of Profitability, Corporate Size, and Public Ownership on the Disclosure of Sustainability Reports Listed in Indonesia - Mediaty, Mediaty; Pratiwi, Nurfadilah (Formosa Journal of Science and Technology, 2023)
This research seeks to explore the impact of profitability, company size, and public ownership on the disclosure of sustainability reports. Employing a quantitative research approach, the study utilizes secondary data sourced from the official Indonesia Stock Exchange (IDX) website. The collected data is then analyzed using the SPSS tool. The research focuses on companies listed in LQ-45 on the IDX during the period 2020-2022, with purposive sampling as the chosen method. The findings of this study reveal the following: (1) Profitability does not exert a significant negative influence on sustainability report disclosure for PT Antam Tbk, PT Perusahaan Gas Negara Tbk, and PT Vale Tbk; (2) Company size demonstrates a significant positive impact on sustainability report disclosure for PT Antam Tbk, PT Perusahaan Gas Negara Tbk, and PT Vale Tbk; (3) Public ownership exhibits a significant negative effect on sustainability report disclosure for PT Antam Tbk, PT Perusahaan Gas Negara Tbk, and PT Vale Tbk.